2015
DOI: 10.1021/acs.jpca.5b10399
|View full text |Cite
|
Sign up to set email alerts
|

Quasiclassical Trajectory Study on the Role of CH-Stretching Vibrational Excitation in the F(2P) + CHD3(v1=0,1) Reactions

Abstract: To analyze the role of CH-stretching vibrational excitation on the reactivity and dynamics of the F((2)P) + CHD3(v1=0,1) reactions, quasiclassical trajectory calculations using a full-dimensional analytical potential energy surface at different collision energies were performed. The extra energy of the CH excitation had almost no effect on the reactivity for the DF + CHD2 channel, although it increased the reactivity for the HF + CD3 channel, with the net effect being that CH excitation barely modified overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
(133 reference statements)
2
14
1
Order By: Relevance
“…The above experimental value is significantly larger than the theoretically calculated F···CH 4 vdW well of 0.48 kcal mol –1 (the exit channel FH···CH 3 complex on the new PES is about 1.4 kcal mol –1 deep) . The latter agrees very well with earlier results of 0.13–0.46 kcal mol –1 . Based on that newly developed PES and a reduced 8D model under C 3 v symmetry, the vibrationally adiabatic potentials for the CH 3 (0 0 ) + DF­( v ) channels are calculated (Figure S1) and predicted an adiabatic well depth of about 4.4 kcal mol –1 for DF­( v = 4). This value compares favorably with another theoretically predicted well of 3.0 kcal mol –1 for the CH 3 (0 0 )·HF­( v = 3) resonant complex .…”
supporting
confidence: 85%
“…The above experimental value is significantly larger than the theoretically calculated F···CH 4 vdW well of 0.48 kcal mol –1 (the exit channel FH···CH 3 complex on the new PES is about 1.4 kcal mol –1 deep) . The latter agrees very well with earlier results of 0.13–0.46 kcal mol –1 . Based on that newly developed PES and a reduced 8D model under C 3 v symmetry, the vibrationally adiabatic potentials for the CH 3 (0 0 ) + DF­( v ) channels are calculated (Figure S1) and predicted an adiabatic well depth of about 4.4 kcal mol –1 for DF­( v = 4). This value compares favorably with another theoretically predicted well of 3.0 kcal mol –1 for the CH 3 (0 0 )·HF­( v = 3) resonant complex .…”
supporting
confidence: 85%
“…However, more recent theoretical investigations, also by QCT but on different PESs in the entrance valley, suggested no inhibitory effect by CHD 3 ( v 1 = 1). 111 , 112 The source of the theory-experiment discrepancy is unclear at present. On the experimental side, it could arise from some other excited methyl products, which are inaccessible to the current REMPI detection method and yet with much higher abundances than those states being probed thus far.…”
Section: Case Studiesmentioning
confidence: 99%
“…A similar problem was found in the study of the F( 2 P) + CH 4 reaction and its isotopic variants, which also presents a high exothermicity, À30.0 kcal mol À1 , and low barrier height, o1 kcal mol À1 . Three full-dimensional PESs were developed for this system by different groups with different strategies, [18][19][20][21] and it was found that small topology changes in the entrance channel can modify the dynamics (excitation function, vibrational distribution of the products, or the scattering distribution).…”
Section: Potential Energy Surfacementioning
confidence: 99%